The prognostic significance of tumor-specific growth factor in colorectal cancer: an observation study - Yanjun Lu; Xinxuan Zhao; Haiyi Liu; Yixun Zhang; Linghong Guo; Lichun Wang (BMC Gastroenterology)
Abstract Background The correlation between tumor-specific growth factor (TSGF) and the prognosis of colorectal cancer (CRC)has not been extensively studied. Research was designed to evaluate the potential of TSGF as a predictive marker for the prognosis of patients with CRC. Methods The serum TSGF was quantified and stratified into elevated/normal groups based on the established threshold detected using the rate method. The log-rank test was employed for survival analysis to evaluate the 3-year overall survival (OS). Prognostic independence was verified through Cox proportional hazards model. The receiver operating characteristic (ROC) curves were plotted to assess the clinical application value of TSGF. Results A total of 2223 patients were incorporated in our study. The survival analysis revealed that elevated TSGF levels were associated with poorer survival in CRC. The multivariate Cox analysis demonstrated TSGF as an independent prognostic factor. The signature covering TSGF with T staging, N staging, CEA, CA199 demonstrated superior predictive capability based on the Area Under the Curve (AUC) (Delong’s test p = 0.025). Conclusion TSGF is an independent factor correlating with the 3-year OS of stage I-III CRC patients. Moreover, our new signature including TSGF can effectively improve the prognostic evaluation of CRC, thereby contributing to precision medication.